2007
DOI: 10.1103/physreva.75.022322
|View full text |Cite
|
Sign up to set email alerts
|

Free-Dirac-particle evolution as a quantum random walk

Abstract: It is known that any positive-energy state of a free Dirac particle that is initially highly localized evolves in time by spreading at speeds close to the speed of light. As recently indicated by Strauch, this general phenomenon, and the resulting "two-horned" distributions of position probability along any axis through the point of initial localization, can be interpreted in terms of a quantum random walk, in which the roles of "coin" and "walker" are naturally associated with the spin and translational degre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…Here Tr c expresses the partial trace for the coin state. Physically speaking, the DTQW can express the free Dirac equation [25][26][27] as follows. We assume the specific quantum coin flip,…”
Section: Discrete Time Quantum Walkmentioning
confidence: 99%
“…Here Tr c expresses the partial trace for the coin state. Physically speaking, the DTQW can express the free Dirac equation [25][26][27] as follows. We assume the specific quantum coin flip,…”
Section: Discrete Time Quantum Walkmentioning
confidence: 99%
“…Despite their contribution to the quantum information processing, quantum walks are themselves very interesting physical systems worth being studied due to effects from various fields of physics like quantum chaos [5] and solid state physics [6]. Recently, it has been shown that discrete time quantum walk (DTQW) resemble the one-dimensional free particle Dirac equation [7,8]. Actually, one has to keep in mind that the idea of quantum walks goes back to Feynmann and Hibbs [9] who considered a discrete version of the one-dimensional Dirac equation propagator.…”
mentioning
confidence: 99%
“…This analysis is similar to Ref. 30 and can be extended to the two-dimensional space [32]. It is emphasized that the DTQW can be implemented under well-controlled nonrelativistic quantum mechanics while the DTQW can simulate the relativistic quantum mechanics.…”
Section: Review Of the Discrete-time Quantum Walkmentioning
confidence: 68%
“…Various DTQWs can simulate the Dirac equation [30][31][32][33][34], the spatially discretized Schrödinger equation [35,36], the Klein-Gordon equation [33,37], or other various differential equations [38,39]. Furthermore, classical dynamics can be simulated [40].…”
Section: Introductionmentioning
confidence: 99%